Resilience or Vulnerability of the Rear-Edge Distributions of Pinus halepensis and Pinus pinaster Plantations Versus that of Natural Populations, under Climate-Change Scenarios. Issue 2 (22nd November 2019) - Silvério, E; Duque-Lazo, J; Navarro-Cerrillo, R M; Pereña, F; Palacios-Rodríguez, G
Abstract: It is predicted that changes in climate will lead to episodes of large forest decline and mortality. Therefore, the distributions of forest plantations and natural stands might already be facing such impacts. We selected the most arid zone of south-eastern Europe (eastern Andalusia) to assess how the distributions of Pinus halepensis Miller. and Pinus pinaster Aiton forest plantations and natural stands cope with climate change and to determine whether natural or planted distributions would be more stable under future climate-change scenarios. We used presence-point locations from natural distributions, obtained from the third Spanish National Forest Inventory, to develop ensemble species distribution models. The forecast predicted a slight increase in the potential distribution of both species by 2040, with a subsequent drastic decrease until 2099. Pinus halepensis had larger current and future potential distributions than P. pinaster but a slightly greater decrease with time in the potential distribution than that of P. pinaster . On the other hand, the natural and planted distributions of P. halepensis were more vulnerable to future climate change scenarios than those of P. pinaster . Natural populations will likely be more resilient to climate change than planted populations.